2016
DOI: 10.1016/j.ejmech.2016.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of tau aggregation using a naturally-occurring cyclic peptide scaffold

Abstract: Disulfide-rich macrocyclic peptides are emerging as versatile scaffolds for the development of stable biochemical tools. This potential is due to the combination of their structural stability and range of bioactivities. Here, we explored the activity of these peptides on fibril growth of the hexapeptide Ac-VQIVYK-NH2 (AcPHF6), which is a tau-derived peptide that has been widely used to understand the pathological mechanism of numerous tauopathies, including Alzheimer's disease. Of the cyclic peptides tested, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 55 publications
1
28
0
1
Order By: Relevance
“…The next step is to decide where the epitope should be grafted onto the scaffold. The possibilities include: insertion between two existing residues of the scaffold; substitution of one or more residues in a single loop 28,37,40,41 ; replacement of residues that span across connected loops 28,49,54 ; or replacement of most of the native residues of the scaffold 33,51 . In the latter two cases, epitope residues that overlap with Cys residues of the scaffold might need to be replaced to retain the number of Cys residues of the scaffold and to enable the formation of the intended disulfide connectivity.…”
Section: The Process Of Molecular Graftingmentioning
confidence: 99%
“…The next step is to decide where the epitope should be grafted onto the scaffold. The possibilities include: insertion between two existing residues of the scaffold; substitution of one or more residues in a single loop 28,37,40,41 ; replacement of residues that span across connected loops 28,49,54 ; or replacement of most of the native residues of the scaffold 33,51 . In the latter two cases, epitope residues that overlap with Cys residues of the scaffold might need to be replaced to retain the number of Cys residues of the scaffold and to enable the formation of the intended disulfide connectivity.…”
Section: The Process Of Molecular Graftingmentioning
confidence: 99%
“…The crystal structure of the PHF6 peptide, describing the steric zipper with a dry interface (42), has spurred a large research effort both to interpret at the structural level aggregation inhibitors described in the past (62)(63)(64) or to rationally develop novel inhibitors (62,65,66). Many of these were tested first in an in vitro assay monitoring the polyanion-induced aggregation of some Tau construct before being tested in a cell model or a transgenic organism.…”
Section: Jbc Reviews: Cryo-em Of Taumentioning
confidence: 99%
“…88 Molecular grafting on the SFTI-1 scaffold has also shown promise in the design of inhibitors of AcPHF6 fibril formation, highlighting their appeal as candidates for inhibition and fibrillation mechanistic studies. 98 Orbitides have been less extensively studied as molecular scaffolds for grafting studies, but they are of interest because they are similar in size to many synthetic cyclic peptides that have been used as probes for understanding and improving the oral bioavailability of peptide-based drugs. For example, White et al synthesised a cyclic N-methylated hexapeptide with oral bioavailability, 99 and Beck et al performed conformational studies and suggested that biologically active sequences could be incorporated into a highly permeable cyclo(-D-Ala-Ala5-) scaffold to enhance oral bioavailability.…”
Section: Synthetic Re-engineering Of Plant Cyclic Peptidesmentioning
confidence: 99%